Analisis Sektor Basis Ekonomi Potensial dan Peluang Kerjasama Regional (Kabupaten Ende - Kabupaten Ngada) - Bhianea, Anastasia Kartina; Nona, Reyna Virginia; Sagajoka, Estherlina (Program Studi Ekonomi Pembangunan Universitas Flores, 2023)
This study aims to find out (1) What economic sector is the basic sector in Ende and Ngada Regencies (2) What is the government's role in increasing the potential economic base and opportunities for cooperation in Ende and Ngada Regencies. The analytical tool used in this research is Location Questionnaire (LQ) analysis. The data used is secondary data in the form of GRDP values for Ende and Ngada Regencies and East Nusa Tenggara Province GRDP at constant prices in 2010 from 2017-2021. The results showed that there were seven (7) basic sectors in Ende Regency with an LQ > 1, namely the Mining and Quarrying, Wholesale and Retail Trade sectors; Car and Motorcycle Repair, Real Estate, Corporate Services, Government Administration, Defense and Compulsory Social Security, Educational Services and Other Services. Meanwhile, there are eight (8) base sectors in Ngada Regency with LQ > 1, namely Agriculture, Forestry and Fishery, Mining and Quarrying, Processing Industry, Water Procurement, Waste Management, Waste and Recycling, Construction, Financial Services and Insurance, Real Estate, Government Administration, Defense and Compulsory Social Security. Based on the percentage results of the two, Ende Regency has a score of 41.17% and Ngada Regency 47.0% which further strengthens local governments so that they need to cooperate for the two regions.